The essence of innovation and its impact on economic growth - Jiyanova, Nargiza Esanboevna; Karimov, Aziza Azamiddin kizi (Science and Education, 2023)
The article discusses concepts that describe the impact of innovation and its financing on the process of economic growth within the state. Theoretical studies of the influence of the volume of financing innovation on economic growth are confirmed by the results of the author’s econometric analysis. It has been established that there is a statistical relationship between the level of economic development and the state of the innovation environment of the national economic system, including the amount of funding for innovation processes.